Peran Jurnalisme Damai dalam Mengatasi Konflik Sosial di Indonesia - Del Piero, Ronald (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
This study examines the role of peace journalism in mitigating social conflicts in Indonesia. Triggered by the high potential for social conflict within the nation's pluralistic society, this research aims to analyze how the practice of peace journalism can be an effective instrument for de-escalating tensions. Using a qualitative approach with a case study strategy, data was collected through in- depth interviews with journalists and media content analysis. The findings indicate that peace journalism plays four crucial roles: promoting understanding, encouraging constructive dialogue, strengthening peace, and preventing violence. Peace journalism is proven to be capable of transforming conflict narratives from being provocative into those that are solution-oriented and focused on reconciliation. The conclusion of this study is that peace journalism is not merely a theory but a vital, transformative practice for building a more tolerant and harmonious society in Indonesia.